2014
DOI: 10.1152/jn.00372.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sensory feedback to ankle plantar flexors is not exaggerated during gait in spastic hemiplegic children with cerebral palsy

Abstract: Willerslev-Olsen M, Andersen JB, Sinkjaer T, Nielsen JB. Sensory feedback to ankle plantar flexors is not exaggerated during gait in spastic hemiplegic children with cerebral palsy. J Neurophysiol 111: 746 -754, 2014. First published November 13, 2013 doi:10.1152/jn.00372.2013.-It is still widely believed that exaggerated stretch reflexes and increased muscle tone in ankle plantar flexors contribute to reduced ankle joint movement during gait in children with cerebral palsy (CP). However, no study has directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
10
37
0
Order By: Relevance
“…This suggests that reflex-mediated stiffness at rest plays no or only a very small role for the functional ability of these patients at least based on the measures that we have included here. This is consistent with other studies, which have failed to find any relation between the extent of spasticity measured biomechanically and the functional ability of patients with spasticity (Sinkjaer et al, 1994, Marsden et al, 2012, Willerslev-Olsen et al, 2014. The finding underscores that spasticity is not the cause of functional impediments by necessity, but may in some cases help to ensure sufficient muscle activity for the patients to maintain upright posture and walk (Dietz, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that reflex-mediated stiffness at rest plays no or only a very small role for the functional ability of these patients at least based on the measures that we have included here. This is consistent with other studies, which have failed to find any relation between the extent of spasticity measured biomechanically and the functional ability of patients with spasticity (Sinkjaer et al, 1994, Marsden et al, 2012, Willerslev-Olsen et al, 2014. The finding underscores that spasticity is not the cause of functional impediments by necessity, but may in some cases help to ensure sufficient muscle activity for the patients to maintain upright posture and walk (Dietz, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…These concerns also challenge previous assumptions regarding the significance of spasticity in the population of people with CP (Willerslev-Olsen et al, 2014). The fundamental problem that these new studies have identified is that muscle resistance caused by pathological changes in passive muscle properties is extremely difficult to distinguish from the muscle resistance caused by hyperactive stretch reflexes, especially since these often co-exist to some extent in many of the patients (Mirbagheri et al, 2004, Lorentzen et al, 2010, Willerslev-Olsen et al, 2013.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[26] Since increased reflex stiffness also appears to play only a small role for the gait disability in the population of adults with CP, this finding is probably of little significance in any case. [9,27,28] The lack of correlation between the reduced passive stiffness and improved gait ability in the training group suggests that other mechanisms contributed to the improvement in gait and may have obscured the contribution from the changes in passive stiffness. Chief among these are changes in the neural drive to the muscles and improved coordination of the muscle activity during gait.…”
Section: Discussionmentioning
confidence: 99%